Music of the Fourth of July a year-by-year chronicle of performances and works composed for the occasion, 1777-2008 - Heintze, James R. (McFarland, 2009)
"The book demonstrates the remarkable significance of music in Fourth of July celebrations from 1777 through 2008. Noteworthy topics and occasions include music at the White House; music by immigrant and ethnic groups; dedications of statues and monuments; symphonies and philharmonic orchestras; the centennial and bicentennial; world's fairs; music in prisons, circuses, and amusement parks; and many others"--Provided by publisher